2014
DOI: 10.1007/s11668-014-9901-8
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Intralaminar Damage and Interlaminar Delamination of Carbon Fiber Composite Laminates Under Three-Point Bending Using Acoustic Emission

Abstract: The complicated failure mechanisms are always distinct features of composite materials which largely affect the stiffness and strength as well as the structural integrity. Yet, until now there are still no mature methods based on various test approaches for accurately predicting the failure mechanisms and damage evolution behaviors of composite structures by considering the effects of loads, environments, and material defects. This research designs and prepares the [0°1 6 //0°1 6 ], [30°1 6 // 30°1 6 ], and [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…According to previous studies, three predominant damage mechanisms were observed in fiber-reinforced composites: matrix cracking, fiber-matrix debonding, and fiber breakage [22,24]. It is also found that the AE signals associated with matrix damage generally correspond to low amplitude and energy values in the ranges of 40-60 dB and 0-2×10 3 aJ, consecutively [33,34]. Similarly, those associated with fiber breakage correspond to high amplitude and energy values in the range of 80-100 dB and above 2.5×10 4 aJ, respectively.…”
Section: K-means Clustering Analysismentioning
confidence: 82%
See 1 more Smart Citation
“…According to previous studies, three predominant damage mechanisms were observed in fiber-reinforced composites: matrix cracking, fiber-matrix debonding, and fiber breakage [22,24]. It is also found that the AE signals associated with matrix damage generally correspond to low amplitude and energy values in the ranges of 40-60 dB and 0-2×10 3 aJ, consecutively [33,34]. Similarly, those associated with fiber breakage correspond to high amplitude and energy values in the range of 80-100 dB and above 2.5×10 4 aJ, respectively.…”
Section: K-means Clustering Analysismentioning
confidence: 82%
“…Similarly, those associated with fiber breakage correspond to high amplitude and energy values in the range of 80-100 dB and above 2.5×10 4 aJ, respectively. And the signal strength and distribution range of the fiber/matrix debonding signals are between the matrix cracking and fiber breakage signals [33][34][35]. Considering the energy and amplitude values of three different clusters presented in Tables 2 and 3, it is concluded that CL-1, CL-2, and CL-3 clusters mainly correspond to matrix cracking, fiber-matrix debonding, and fiber breakage damages, respectively.…”
Section: K-means Clustering Analysismentioning
confidence: 90%
“…In [], the authors analyze the fiber reinforced plastic failure in the form of delamination by the method of acoustic emission under conditions of a three‐point bending. The parameters of acoustic emission, which allow determining the type and size of developing failure, are identified.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance against the delamination is characterized by mode-I (Jumel et al, 2011a,b;Salem et al, 2013;Kim et al, 2011;Peng et al, 2011;Gracia et al, 2015) mode-II (Arrese et al, 2010;Argüelles et al, 2011;Yoshihara and Satoh, 2009;Rizov and Mladensky, 2012) mode-III (Rizov et al, 2006;Szekr enyes, 2009aSzekr enyes, , 2011aRodríguez-Gonz alez et al, 2014;Khoshravan and Moslemi, 2014;L opez-Men endez et al, 2014;Marat-Mendes and Freitas, 2009;Mehrabadi and Khosravan, 2013;Yoshihara, 2006) mixed-mode I/II (de Baere et al, 2012;Davidson et al, 2009;Fern andez et al, 2013;Islam and Kapania, 2014;Peng et al, 2012;Kenane et al, 2010;Marat-Mendes and Freitas, 2010;Nikbakht et al, 2010;Nikbakht and Choupani, 2008;Plain and Tong, 2011;Liu et al, 2015;Pereira et al, 2014) mixedmode II/III (Szekr enyes, 2007;Kondo et al, 2011Kondo et al, , 2010Mladensky and Rizov, 2013;Kotousov et al, 2013Kotousov et al, , 2012Szekr enyes, 2012;Mehrabadi, 2013Mehrabadi, , 2014Miura et al, 2012;Takeda et a...…”
Section: Introductionmentioning
confidence: 99%
“…It has also to be mentioned that coupled multilayer/interface models have already been introduced in the literature, which are able to provide accurate energy release rate (ERR) calculations compared to FE models using solid type elements (Bruno and Greco, 2001;Bruno et al, 2003Bruno et al, , 2005). An important aspect of these formulations is that it avoids the complications arising from the oscillatory singularities for a delamination between different materials.The delaminations may take place because of low-velocity impact (Ganapathy and Rao, 1998; Rizov et al Peng et al, 2012;Kenane et al, 2010;Marat-Mendes and Freitas, 2010;Nikbakht et al, 2010;Nikbakht and Choupani, 2008;Plain and Tong, 2011;Liu et al, 2015;Pereira et al, 2014) mixedmode II/III (Szekr enyes, 2007;Kondo et al, 2011Kondo et al, , 2010Mladensky and Rizov, 2013;Kotousov et al, 2013Kotousov et al, , 2012Szekr enyes, 2012;Mehrabadi, 2013Mehrabadi, , 2014Miura et al, 2012;Takeda et al, 2013;Suemasu et al, 2010) The previous developments e that this paper is based on e are summarized as follows: In some recent papers the so-called interface constraints were applied to model delaminated composite plates by CLPT, FSDT, SSDT and TSDT with midplane cracks and symmetric lay-up (Szekr enyes, 2014a(Szekr enyes, ,c,e, 2013a. Later, the models were generalized to asymmetrically delaminated plates and the socalled system of exact kinematic conditions (SEKC) was proposed for the FSDT (Szekr enyes, 2013b), SSDT (Szekr enyes, 2014b) and Reddy third-order theory (Szekr enyes, 2014d).…”
mentioning
confidence: 99%